Editorial Comment on the Article by P.A. Ivanov et al. “A New Method of Intraoperative Reposition and Holding of Bone Fragments with Ty-Raps” - Andrei P. Sereda (Travmatologiâ i Ortopediâ Rossii, 2021)
In the editorial comment on the article A New Method of Intraoperative Reposition and Holding of Bone Fragments with Ty-Raps the advantages and disadvantages of the authors method are discussed. The advantages include availability, low cost, convenience and reliability. At the same time, it may lead to excessive devascularization of bone fragments with the risk of delayed union or even non-union. Only a comparative study on a large number of patients can confirm or refute these concerns. The comment also contains a brief review of articles on this issue.